Engaging Universities and Ministry of Health in Evaluation of Reformed Community Medicine Training Program - Madiha Said Abdelrazik; Doa’a Ahmed Saleh; Rehab Abdelhai Ahmed (Journal of High Institute of Public Health, 2009)
Background: Reform of the community medicine training program (CMTP) for the undergraduate medical students is crucial for successful medical education and community development. Objective To evaluate the practical component of the reformed CMTP by: 1) reviewing the students' performance, 2) exploring the perspectives of the public health department (PHD) staff at Cairo and Ain-Shams Universities towards the program 3) exploring the views of the managers of the Ministry of Health (MOH) Primary Health Care (PHC) centers where medical students receive their PHC training towards the program. Methods: Quantitative data were obtained by reviewing the performance scores of 1492 students. Qualitative data were obtained by focus group discussions with PHD staff and MOH PHC managers. Results: It was found that the total students' mean score was 94.2%. About 91% of students scored >85% of the total marks. PHD staff from both universities expressed appreciation to the introduction of generic skills in the CMTP. They referred the success in management of CMTP to small-group teaching. The community-oriented and service-learning approaches also added more points to the CMTP. The MOH PHC managers acknowledged the CMTP which would contribute to preparing future physicians to have vital role in the dynamic health system.